THE PSYCHOLOGY OF INDIVIDUAL DIFFERENCES (Spectrum Journal of Innovation, Reforms and Development, 2024)
The psychology of individual differences is a field of psychology that studies the differences between people in their psychological characteristics. These differences may relate to cognitive abilities, personality traits, emotional reactions, motivation, and other aspects of behavior and the psyche.